Barriers to Election Day Voting Among Medical Students [06G]. (May 2020) - Hotz, Melanie; Yang, David; Solomon, Abigail; Hagan, Joseph; Tanner, La'Nasha
Abstract : INTRODUCTION: Laws enacted by elected officials can affect how physicians practice. Although civic engagement is a value emphasized throughout medical training, physicians have been found less likely to vote in national elections. Little research has been conducted looking into factors that contribute to low medical trainee or physician voter turnout. This study was designed to look at what barriers medical students encounter that may prevent them from voting in elections. METHODS: An anonymous online survey was emailed to Medical Students at two Medical Schools in the spring of 2019. The survey assessed demographic information and barriers students encountered related to voting in recent elections. RESULTS: 353 medical students responded to the survey. 29% (104/352) of respondents did not vote in the 2018 Midterm election. 14% (50/352) of respondents did not vote in the 2016 Presidential election. The most prevalent voting barriers included limited time to learn about the candidates (35%, 124/353) and amendments (31%, 111/353). While 15.3% (54/353) of respondents reported that schools reminded them to vote, only 3.4% (12/353) reported that school provided time away from academic or clinical responsibilities to vote. CONCLUSION: Given the value that medical schools place on civic engagement, it is surprising that so few students are given time to vote. Medical schools can possibly enhance voter turnout by reminding students of upcoming elections and providing protected time to participate in elections. By reducing barriers to voting for medical trainees, medical schools can help create a generation of future physicians with a higher voter turnout.